IMPLEMENTASI PRINSIP COMMON BUT DIFFERENTIATED RESPONSIBILITIES SEKTOR PERKEBUNAN DALAM MITIGASI PERUBAHAN IKLIM DI INDONESIA - Sitompul, Melani Aronica Maya Sari Br.; Jayakusuma, Zulfikar; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia ratified the Climate Change Convention with Law Number 6 of 1994 and Kyoto Protocol with Law Number 17 of 2004, so that Indonesia continues to participate to minimize Greenhouse Gases. The Climate Change Convention adopts several important principles in climate change mitigation policy efforts. One of the principles adopted in this convention is the principle of Common but Differentiated Responsibilities (CBDR) or other terms Joint but Different Responsibilities. Where Indonesia as one of the countries included in the category of developing countries legally does not have the obligation to reduce emissions, because in the provisions of the Kyoto Protocol, developing countries are not required to reduce emissions. However, even though the Indonesian State does not have the obligation to reduce its emissions, it must still participate in maintaining its emissions not to increase. Indonesia's commitment to reduce greenhouse gas (GHG) emissions by 29% under Business as Usual (BAU) in 2030 and up to 41% with international assistance.This type of research can be classified as normative juridical research, because this research is carried out by examining library materials or secondary data, so that it can be called normative legal research or library law research.From the results of the study, the international aid commitments in the form of financial assistance and technological assistance. As well as commitments from Indonesia in the form of making national regulatory policies, budgeting, and making climate change program strategies. However, despite the commitment of both Indonesia and the Climate Change Convention, it still has obstacles, namely, First, the rate of deforestation continues to increase. Second, there are policy differences between the climate change conventions and the Indonesian government. Third, the weak moratorium on forest areas and oil palm plantations. And Fourth, there are overlapping permits for the opening of oil palm plantations which occur every year.Keywords: Climate Change-Mitigation-CBDR-Oil Palm Plantations